MO713ENCAPSULATING PERITONEAL SCLEROSIS IN KIDNEY TRANSPLANT RECIPIENTS. (29th May 2021) - Ouertani, Imen; Awatef, Azzabi; Wissal, Sahtout; Narjes, Ben Aicha; Sanda, Mrabet; Sabri, Ferdawes; Dorsaf, Zellema; Yosra, Guedri; Achour, Abdelatif
Abstract: Background and Aims: Encapsulating peritoneal sclerosis (EPS) is a life-threatening complication of long-term peritoneal dialysis (PD). Causative factors are the chronic exposure to bioincompatible PD and peritonitis episodes. Pro-inflammatory state and oxidative stress associated with chronic uremia may further accelerate these pathomechanisms. Clinical symptoms are, essentially, signs of intestinal obstruction. Treatments commonly used are corticosteroids, tamoxifen, immunosuppressants like azathioprine, mycophenolate mofetil (MMF), or mTOR inhibitors which has fibrinolytic properties and may help with reducing inflammation. In the last ten years, the incidence of SEP in kidney transplant recipients has increased, but few cases have been reported. Given the rare nature of this pathology, we decided to publish the cases of two EPS happening after kidney transplantation (KT). Case report: We report the cases of two male patients aged 46 and 25 with a history of chronic renal failure, who benefited of continuous ambulatory peritoneal dialysis (CAPD) for three years. The first patient was switched to haemodialysis (HD) for sub-dialysis, with one episode of peritonitis and one episode of catheter infection. The second patient had three episodes of peritonitis complicated by asymptomatic EPS, hence its transfer to HD. Our two patients presented, at 30 and 40 days post KT, an episode of acute intestinal obstruction with abdominal scans fitting with a mechanical bowel obstruction on an encapsulating peritonitis without signs of complication. Both patients were on corticosteroid therapy (15 and 17.5 mg/day) combined with MMF and Calcineurin inhibitors (CNIs) (Tacrolimus). Medical measures were not effecient. Surgical treatment was then considered. During the operation, a classical picture of EPS was found characterized by a thin cocoon-like sclerotic membrane encasing the small bowel. A complete resection of the encapsulating sclerotic membrane and total adhesiolysis were performed, with an immediate improvement on the clinical level. No recurrence was noted for both patients at 5 and 24 months respectively. Conclusion: The specificities of our patients compared to the reported cases were the short duration of the PD and the relatively young age. In fact, some studies demonstrated an increased incidence of EPS in younger patients. In addition, this complication has declared itself despite corticosteroid therapy. Some case reports have demonstrated an increase in the incidence of SEP in kidney transplant patients, suggesting the possible implication of CNIs which have a profibrotic effect and may promote peritoneal matrix accumulation.